2018
DOI: 10.1111/srt.12443
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dermal structure and skin oxidative stress in overweight and obese Japanese males after weight loss: a longitudinal observation study

Abstract: The dermal structure in the thighs of overweight young individuals can be improved to the level of the structure in those of normal body weight individuals following weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
2
3
1
Order By: Relevance
“…Our data contrasts with a Japanese study in which skin taken from women undergoing breast reconstruction showed a shift to greater epidermal thickness in the obese when compared to non-obese subjects, but the variation was very large [24]. In another study in obese subjects in which dermal structure in abdominal skin was visualized as echogenicity using ultrasound scanners, weight reduction decreased dermal thickness in about half of the subjects [25]. A previous study also observed no increase in skin thickness in obese subjects weighing up to 200 kg.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data contrasts with a Japanese study in which skin taken from women undergoing breast reconstruction showed a shift to greater epidermal thickness in the obese when compared to non-obese subjects, but the variation was very large [24]. In another study in obese subjects in which dermal structure in abdominal skin was visualized as echogenicity using ultrasound scanners, weight reduction decreased dermal thickness in about half of the subjects [25]. A previous study also observed no increase in skin thickness in obese subjects weighing up to 200 kg.…”
Section: Discussioncontrasting
confidence: 99%
“…41 has been reported to reverse some aspects of obesity-linked dermal changes. 44 The present findings extend our understanding of the impact of obesity and overweight on skin properties as assessed via TDC measurements.…”
Section: Discussionsupporting
confidence: 71%
“…Alterations in skin microcirculation of obese persons have also been reported, and obesity has been linked to several skin dermatoses and conditions . Weight loss has been reported to reverse some aspects of obesity‐linked dermal changes . The present findings extend our understanding of the impact of obesity and overweight on skin properties as assessed via TDC measurements.…”
Section: Discussionsupporting
confidence: 66%
“…In another study on obese (BMI 35-50) and non-obese postmenopausal women between the ages of 40 and 70 years, no differences in relation to the thickness of the epidermis between those groups were found, despite existing differences in gene expression profile (Walker et al, 2020). Furthermore, another study by Matsumoto et al, revealed that weight reduction leads to a decrease in epidermal thickness by about 50% of analysed obese males (Matsumoto et al, 2018). It is also worth mentioning that in some previously published studies, the BMI of analyzed patients is not given.…”
Section: Discussionmentioning
confidence: 93%